Molecular mechanisms in liver repair and regeneration: from physiology to therapeutics - Xiao Ma; Tengda Huang; Xiangzheng Chen; Qian Li; Mingheng Liao; Li Fu; Jiwei Huang; Kefei Yuan; Zhen Wang; Yong Zeng (Signal Transduction and Targeted Therapy)
Abstract Liver repair and regeneration are crucial physiological responses to hepatic injury and are orchestrated through intricate cellular and molecular networks. This review systematically delineates advancements in the field, emphasizing the essential roles played by diverse liver cell types. Their coordinated actions, supported by complex crosstalk within the liver microenvironment, are pivotal to enhancing regenerative outcomes. Recent molecular investigations have elucidated key signaling pathways involved in liver injury and regeneration. Viewed through the lens of metabolic reprogramming, these pathways highlight how shifts in glucose, lipid, and amino acid metabolism support the cellular functions essential for liver repair and regeneration. An analysis of regenerative variability across pathological states reveals how disease conditions influence these dynamics, guiding the development of novel therapeutic strategies and advanced techniques to enhance liver repair and regeneration. Bridging laboratory findings with practical applications, recent clinical trials highlight the potential of optimizing liver regeneration strategies. These trials offer valuable insights into the effectiveness of novel therapies and underscore significant progress in translational research. In conclusion, this review intricately links molecular insights to therapeutic frontiers, systematically charting the trajectory from fundamental physiological mechanisms to innovative clinical applications in liver repair and regeneration.